2011
DOI: 10.1177/1545968311400091
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Lumbosacral Nerve Magnetic Stimulation Improves Bladder Dysfunction Due to Lumbosacral Nerve Injury

Abstract: rLMS at 15 Hz may improve urinary dysfunction secondary to lumbosacral nerve injury. Further trials can determine the profile of patients who may benefit and optimal stimulation parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
10
0
4
Order By: Relevance
“…Improved urinary symptoms were seen when patients with intractable neurogenic urinary bladder dysfunction secondary to lumbosacral nerve injuries were treated with 15-Hz rLSMS. 21 Furthermore, sacral nerve stimulation (SNS) has been reported to produce significant pain reduction in patients with chronic functional anorectal pain disorders not responding to conventional treatments. 6,15 Moreover, in a series of studies, Fassov et al, [7][8][9] found that SNS could induce thermal and biomechanical changes in rectal function alongside improvements in symptoms and quality of life in patients with IBS during the on-phase of SNS but no effects on small bowel motility.…”
Section: Discussionmentioning
confidence: 99%
“…Improved urinary symptoms were seen when patients with intractable neurogenic urinary bladder dysfunction secondary to lumbosacral nerve injuries were treated with 15-Hz rLSMS. 21 Furthermore, sacral nerve stimulation (SNS) has been reported to produce significant pain reduction in patients with chronic functional anorectal pain disorders not responding to conventional treatments. 6,15 Moreover, in a series of studies, Fassov et al, [7][8][9] found that SNS could induce thermal and biomechanical changes in rectal function alongside improvements in symptoms and quality of life in patients with IBS during the on-phase of SNS but no effects on small bowel motility.…”
Section: Discussionmentioning
confidence: 99%
“…• подавлению обратного нейронального захвата норадреналина и серотонина [45]; • стимуляции афферентных волокон пудендаль-ного нерва в составе крестцовых корешков [46]; • активации спинальной опиодной системы, подавляющей сокращения детрузора [47]; • стимуляции эфферентных волокон тазового нерва в составе крестцовых корешков [48]. В исследовании P. M. Braun и соавт.…”
Section: Sacral Micturition Centerunclassified
“…При клинически противоположных формах нейро-генных расстройств мочеиспускания во многих иссле-довательских работах наблюдался положительный терапевтический эффект сакральной МС, что может быть объяснено активацией различных регуляторных рефлексов в ответ на стимуляцию одних и тех же структур [48][49][50].…”
Section: Sacral Micturition Centerunclassified
“… Fujishiro et al (2002) reported that magnetic stimulation of the sacral roots for the treatment of urinary frequency and urge incontinence produced a useful improvement in symptoms. Khedr et al (2011) also found that repetitive lumbosacral root magnetic stimulation (rLMS) at 15 Hz may improve urinary dysfunction secondary to lumbosacral nerve injury. A comparative study investigating the urodynamic effects of functional magnetic stimulation (FMS) (pulsegen device) and functional electrical stimulation (FES) (a vaginal electrode in women and a surface electrode on the dorsal part of the penis in men) found that both treatments reduced detrusor overactivity with FMS being slightly superior to FES ( Yamanishi et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, magnetic stimulation has been proposed as a potential method for stimulation of sacral nerves ( Khedr et al, 2011 ). It is believed to have the same underlying effect as functional electrical stimulation since it generates an electrical field resulting similar to that produced by conventional electrical stimulators ( Karim et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%